Aspergillosis and stem cell transplantation: An overview of experimental pathogenesis studies. Issue 8 (16th November 2016) - Al-Bader, Nadia; Sheppard, Donald C.
ABSTRACT: Invasive aspergillosis is a life-threatening infection caused by the opportunistic filamentous fungus Aspergillus fumigatus . Patients undergoing haematopoietic stem cell transplant (HSCT) for the treatment of hematological malignancy are at particularly high risk of developing this fatal infection. The susceptibility of HSCT patients to infection with A. fumigatus is a consequence of a complex interplay of both fungal and host factors. Here we review our understanding of the host-pathogen interactions underlying the susceptibility of the immunocompromised host to infection with A. fumigatus with a focus on the experimental validation of fungal and host factors relevant to HSCT patients. These include fungal factors such as secondary metabolites, cell wall constituents, and metabolic adaptations that facilitate immune evasion and survival within the host microenvironment, as well as the innate and adaptive immune responses involved in host defense against A. fumigatus .